2023
DOI: 10.3390/ijms24065176
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium vaccae NCTC 11659, a Soil-Derived Bacterium with Stress Resilience Properties, Modulates the Proinflammatory Effects of LPS in Macrophages

Abstract: Inflammatory conditions, including allergic asthma and conditions in which chronic low-grade inflammation is a risk factor, such as stress-related psychiatric disorders, are prevalent and are a significant cause of disability worldwide. Novel approaches for the prevention and treatment of these disorders are needed. One approach is the use of immunoregulatory microorganisms, such as Mycobacterium vaccae NCTC 11659, which have anti-inflammatory, immunoregulatory, and stress-resilience properties. However, littl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 95 publications
0
5
0
Order By: Relevance
“…Studies using M. vaccae NCTC 11659 in vivo have shown that, in the absence of subsequent stress exposure or LPS challenge, M. vaccae NCTC 11659 has an adjuvant-like effect, e.g., increasing bronchopulmonary Il1b , Il6 , and Tnf mRNA expression 12 h to 3 days following intratracheal administration [ 25 ] and resulting in a persistent increase in the secretion of IL-6 from mesenteric lymph node cells stimulated with an anti-CD3 antibody in vitro [ 11 ] or a persistent increase in hippocampal Il6 mRNA expression [ 20 ]. Likewise, in vitro studies have revealed that the treatment of human THP-1-derived-macrophages with M. vaccae NCTC 11659 increases the expression of genes involved in proinflammatory signaling, including Il1b , Ccl2 , and numerous other canonical inflammatory markers [ 19 ] (Holbrook et al, 2023). In the present study, 48 h following the exposure of BV-2 cells to 100 µg/mL M. vaccae NCTC 11659, 5 of the 248 endogenous genes in the CodeSet (i.e., 2%) were differentially expressed ( p < 0.05 and fold change either less than –1.5 or greater than 1.5) within the CMV groups between M. vaccae NCTC 11659 conditions (i.e., 100 µg/mL M. vaccae NCTC 11659/CMV vs. BBS/CMV) ( Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies using M. vaccae NCTC 11659 in vivo have shown that, in the absence of subsequent stress exposure or LPS challenge, M. vaccae NCTC 11659 has an adjuvant-like effect, e.g., increasing bronchopulmonary Il1b , Il6 , and Tnf mRNA expression 12 h to 3 days following intratracheal administration [ 25 ] and resulting in a persistent increase in the secretion of IL-6 from mesenteric lymph node cells stimulated with an anti-CD3 antibody in vitro [ 11 ] or a persistent increase in hippocampal Il6 mRNA expression [ 20 ]. Likewise, in vitro studies have revealed that the treatment of human THP-1-derived-macrophages with M. vaccae NCTC 11659 increases the expression of genes involved in proinflammatory signaling, including Il1b , Ccl2 , and numerous other canonical inflammatory markers [ 19 ] (Holbrook et al, 2023). In the present study, 48 h following the exposure of BV-2 cells to 100 µg/mL M. vaccae NCTC 11659, 5 of the 248 endogenous genes in the CodeSet (i.e., 2%) were differentially expressed ( p < 0.05 and fold change either less than –1.5 or greater than 1.5) within the CMV groups between M. vaccae NCTC 11659 conditions (i.e., 100 µg/mL M. vaccae NCTC 11659/CMV vs. BBS/CMV) ( Figure 3 A).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that 250 ng/mL LPS ( Escherichia coli 0111:B4) potently induces inflammation in BV-2 microglial cells and human THP-1-derived macrophages [ 19 , 21 , 28 ]. Twenty-four hours following the exposure of BV-2 cells to 250 ng/mL LPS, relative to CMV control conditions, 71 of the 248 endogenous inflammation-related genes in the CodeSet (i.e., 28.6%) were differentially expressed, as assessed by a moderated t -test (i.e., satisfied the criteria of p < 0.05 and fold change either less than –1.5 or greater than 1.5) (i.e., BBS/250 ng/mL LPS vs. BBS/CMV) ( Figure 3 B).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations